Monomeric C-Reactive Protein: Current Perspectives for Utilization and Inclusion as a Prognostic Indicator and Therapeutic Target - Slevin, Mark; Heidari, Nima; Azamfirei, Leonard (Frontiers in Immunology, 2022)
Monomeric C-reactive protein (mCRP), once thought to be a figment of the imagination and whose biological activity was ascribed to its sodium azide preservative, has now pronounced itself as a critical molecule playing a direct role in mediating many of the acute and chronic aberrant pathological responses to inflammation. In this focused mini review, we describe the currently attributed pathobiological interactions of mCRP in disease, where its tissue and cellular distribution and deposition have recently been clearly characterized and linked to inflammation and other pathway-associated progression of neurological and cardiovascular complications and deleterious outcomes. and focus upon current opinions as to the diagnostic and prognostic potential of mCRP-plasma circulating protein and define the possible future therapeutics including ongoing research attempting to block CRP dissociation with small molecule inhibitors or prevention of cell surface binding directly using antibodies or modified orphan drug targeting directed towards CRP, inhibiting its cellular interactions and signaling activation. There is no doubt that understanding the full influence of the biological power of mCRP in disease development and outcome will be considered a critical parameter in future stratified treatment.